2017
DOI: 10.21451/1984-3143-ar799
|View full text |Cite
|
Sign up to set email alerts
|

Influences of different space allowance on reproductive performances in buffalo

Abstract: The aim of this study was to evaluate the effect of two different conditions of space allowance on reproductive performance and oxidative parameters, biochemical and hormonal profiles in buffalo. The trial was carried out on one hundred pluriparous buffaloes divided into two different groups. Buffaloes in group HDG (high density group -n = 50) were maintained in open yards that allowed 10 m 2 /head while those in group LDG (low density group -n = 50) were maintained in 22 m 2 /head. After 60 days, 45 buffaloes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…In order to circumvent this, double inseminations, with 12 hour interval, after initiation of estrus, were adopted in buffalo (Neglia et al, 2003;Naseer et al, 2011). Pregnancy rate were reported to be fairly high (upto 60 %) in synchronized and (upto 80%) in resynchronized buffalo with fix time inseminations (de Araujo Berber et al, 2001;Baruselli et al, 2001;Warriach et al, 2008;Salzano et al, 2017;Arshad et al, 2017). The higher pregnancy rate, achieved at 24 hours with single AI in this study, is perhaps due to artificial insemination time with regard to timing of ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to circumvent this, double inseminations, with 12 hour interval, after initiation of estrus, were adopted in buffalo (Neglia et al, 2003;Naseer et al, 2011). Pregnancy rate were reported to be fairly high (upto 60 %) in synchronized and (upto 80%) in resynchronized buffalo with fix time inseminations (de Araujo Berber et al, 2001;Baruselli et al, 2001;Warriach et al, 2008;Salzano et al, 2017;Arshad et al, 2017). The higher pregnancy rate, achieved at 24 hours with single AI in this study, is perhaps due to artificial insemination time with regard to timing of ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Animal welfare has become an important consideration in contemporary intensive livestock production systems, recognizing the fundamental role of welfare in animal health, productivity, and product quality and safety (Broom, 2010). One study showed that the amount of milk produced by buffalo cows did not differ for animals allocated 10 or 22 m 2 of space per animal (Salzano et al, 2017). However, the quality of buffalo milk is arguably more important than the quantity.…”
Section: Short Communicationmentioning
confidence: 99%
“…Some of these consequences are related to the increase in prolactin levels observed during the long photoperiod season, which are related to a decrease in gonadotropin secretion, a decrease in the follicular steroidogenic capacity, generating anestrus and infertility [74,75]. Additionally, during the long photoperiod season, the corpus luteum receives lower blood flow, which compromises its ability to produce progesterone, which is related to embryos of smaller size, which are more prone to embryonic death [69,[76][77][78][79][80]. The season did not affect buffalo heifer's fertility, probably because they have higher levels of melatonin during the hours of light in comparison with buffaloes, which have previously had a calf [64,202].…”
Section: Season Of Calvingmentioning
confidence: 99%
“…The season did not affect buffalo heifer's fertility, probably because they have higher levels of melatonin during the hours of light in comparison with buffaloes, which have previously had a calf [64,202]. The better reproductive efficiency observed in the short photoperiod season could be related to the decrease in temperature, relative humidity, and temperature-humidity index (THI) [53,80]. Dash et al [81] observed a negative relationship between THI and pregnancy rate in Murrah buffaloes, with a significant decrease in this parameter when THI was higher than 75.…”
Section: Season Of Calvingmentioning
confidence: 99%